Use of assessment to reinforce patient safety as a habit. (1st December 2006) - Galbraith, R M; Holtman, M C; Clyman, S G
Abstract : The US spends far more than any other nation on health care. Physicians undergo lengthy and comprehensive training that is carefully scrutinized, and are held to high standards in national examinations. At best the care delivered matches or exceeds that in any other country. And yet, often simple preventable medical errors occur at alarming and unacceptable rates. The public, corporate consumers of health care, large payors and malpractice insurance carriers are all becoming impatient with the pace of improvement. The medical profession recognizes that dealing with this problem is an urgent priority and is grappling to find the best approaches. This paper focuses on the constructive use of assessment to embed a pervasive and proactive culture of patient safety into practice, starting with the trainee and extending out into the practice years. This strategy is based on the adage that "assessment drives curriculum" and proposes a series of new assessment tools to be added to all phases of the training-practice continuum.